Differences in rotations between the winning and losing teams at the youth European volleyball championships for girls - Zadraznik, M.; Marelic, N.; Resetar, T. (Acta Universitatis Palackianae Olomucensis. Gymnica, 2009)
BACKGROUND: Researchers of the game of volleyball often study the differences that separate the winning and losing teams. Namely, the volleyball game runs in two complexes (K1 - game after receive of serve: serve - receipt of serve - setting the attack - attack; K2 - game after own serve: serve - block - defence - counter attack), in addition the players have to rotate in accordance with the rules of the game of volleyball. Playing situations in six rotations do not equally correlate to K1 and K2 in their tactical aspect, nor are they of the same difficulty. OBJECTIVES: The study examined whether there are statistically significant differences in the phases of a volleyball game between the winners and losers for each of the six volleyball rotations separately. Differences in individual rotations between winning and losing teams were examined. For rotations with statistically significant differences between the teams, the phases that determine those differences the most were also researched. METHODS: The study was carried out at the European youth volleyball championships for women. Twenty games were analysed, a five level scale was used to evaluate the successfulness of the game for 98 under 18 years old women players. Six phases of the volleyball game were analysed: serve, receipt of serve, attack in K1, attack in K2, block and defence (attack receipt). A criterion variable was represented with each individual rotation. Simple descriptive statistical parameters were calculated together with six canonical discriminant analyses, one for each of the volleyball rotations. RESULTS: The results of canonical discriminatory analysis revealed that four out of six volleyball rotations were statistically significant at the level of p < 0.05 (rotation 1 = 0.02; rotation 2 = 0.00; rotation 3 = 0.00; rotation 6 = 0.04). It is interesting to notice that different game phases show the largest projection of discriminatory function exactly in the rotations with statistically significant differences. They were: receipt of serve and attack in K1 and K2 for rotation 1, receipt of serve, block and defence for rotation 2, serve and defence for rotation 3, attack in K1 for rotation 6. CONCLUSIONS: These results point to the specific characteristics of individual rotations in this age period, which have to be considered in the organisation of the training process. The results undoubtedly indicate that in the process of the synchronisation of team play, each of the six rotations require specific attention both in the technical and tactical sense.